PEREMPUAN DAN ISU LINGKUNGAN (Analisis Pemberitaan di Media Nasional dan Lokal tahun 2014-2017) - Kurniasari, Netty Dyah (UIN Sunan Kudus, 2017)
Women have always been described as marginalized. Various studies and research on the image (representation) of women in the media always put women as objects. Media can construct the reality that occurs so as to affect the perception of the audience. This study aims to find out how the media describes news about women and environmental issues. The chosen method is textual analysis by analyzing existing text on women and environmental issues. The selected media are Kompas, Tempo, TribunNews, Antara and Radar Madura (representing local media). News selected from the year 2014 on the grounds because the news about environmental issues in Madura many covered Radar Madura in 2014. The results showed that the majority of all media describe women as the object (victims) who always ask for help and do not have the initiative to overcome problems. While men are described as the problem solver. However, national media such as Kompas tend to describe balanced women (as objects and subjects). In contrast, local media ( Radar Madura) all portray women as objects of narrators whose ultimate purpose is to raise the value of news.